2022
DOI: 10.3390/ijms23116235
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomics of Bioactive Lipids in Alzheimer’s and Parkinson’s Diseases: Where Are We?

Abstract: Lipids are not only constituents of cellular membranes, but they are also key signaling mediators, thus acting as “bioactive lipids”. Among the prominent roles exerted by bioactive lipids are immune regulation, inflammation, and maintenance of homeostasis. Accumulated evidence indicates the existence of a bidirectional relationship between the immune and nervous systems, and lipids can interact particularly with the aggregation and propagation of many pathogenic proteins that are well-renowned hallmarks of sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 156 publications
0
13
0
Order By: Relevance
“…In accordance, higher plasma levels of pro‐inflammatory mediators such as IL‐1β, IL‐2, IL‐8, IL‐6, IL‐17, TNF‐α, iNOS, COX‐1, and COX‐2 have been shown to augment the dopaminergic neurons injuries in PD 59–62 . A review of recent findings shows that several SPMs have beneficial effects on PD, and have a key role in the pathogenesis of PD 12 . Krashia et al showed that patients with PD had higher levels of TNF‐α, interferon‐γ (IFN‐γ), IL‐4, and IL‐10 in the plasma and CSF with significantly lower RvD1 levels than their control subjects 63 .…”
Section: Parkinson's Diseasementioning
confidence: 77%
See 3 more Smart Citations
“…In accordance, higher plasma levels of pro‐inflammatory mediators such as IL‐1β, IL‐2, IL‐8, IL‐6, IL‐17, TNF‐α, iNOS, COX‐1, and COX‐2 have been shown to augment the dopaminergic neurons injuries in PD 59–62 . A review of recent findings shows that several SPMs have beneficial effects on PD, and have a key role in the pathogenesis of PD 12 . Krashia et al showed that patients with PD had higher levels of TNF‐α, interferon‐γ (IFN‐γ), IL‐4, and IL‐10 in the plasma and CSF with significantly lower RvD1 levels than their control subjects 63 .…”
Section: Parkinson's Diseasementioning
confidence: 77%
“…They mostly induce significant anti‐inflammatory responses that favor the prevention of AD. For a review of recent findings, see Chiurchiù et al 12 It should be noted that Aβ is an activator of ALX/FPR2 that promotes chemotaxis and oxidative stress and activates microglia 42 . During neuroinflammation, Aβ and pro‐inflammatory chemokines efflux across the BBB and promote the recruitment of leukocytes into the CNS to modulate neuroinflammation and neurodegeneration 43 .…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, the lipid content of membrane lipid rafts is directly linked to amyloidogenesis, a significant pathogenetic component for AD (Ehehalt et al, 2003), which have a higher concentration of saturated fatty acids (FAs) than Frontiers in Genetics frontiersin.org polyunsaturated fats (PUFAs) and sphingolipids, which operate as platforms for Aβ associations with tau and ApoE to facilitate the formation of A oligomers and hyperphosphorylation (Di Paolo and Kim 2011;Huynh et al, 2017). In addition, cortical and free unsaturated FAs induce the assembly of amyloid and tau filaments in vitro (Chiurchiù et al, 2022).…”
Section: Lipidomics In Alzheimer's Diseasementioning
confidence: 99%